Unite for a Better Life, a gender-transformative educational intervention targeting prevention of intimate partner violence and HIV risk behaviors in Ethiopia - CGIAR Research Program on Policies, Institutions, and Markets (2020)
The results were disseminated through the UN Women RESPECT framework. The intervention materials are being adopted in other settings.